2015
DOI: 10.1111/nyas.12968
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β‐catenin signaling plays a key role in the development of spondyloarthritis

Abstract: Spondyloarthritis (SpA) is a group of diseases consisting of psoriatic arthritis (PsA), reactive arthritis, arthritis related to inflammatory bowel disease (a subgroup of juvenile idiopathic arthritis), and ankylosing spondylitis (the prototype of SpA). Axial bone formation and the combination of concurrent erosion and new bone formation are specific characteristics of SpA disease. The use of anti-proinflammatory cytokines, such as inhibitors of tumor necrosis factor α (TNF-α), appears to be the greatest advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 74 publications
(151 reference statements)
3
32
0
1
Order By: Relevance
“…It is well known that the pathogenesis of AS is characterized by three phases: inflammation, erosion and abnormal bone outgrowth [32]. In this regard our data seem to recapitulate all these pathogenetic stages, showing deregulation of genes involved in the inflammatory process as well of transcripts that play a role in bone remodeling (i.e., bone growth and bone erosion).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is well known that the pathogenesis of AS is characterized by three phases: inflammation, erosion and abnormal bone outgrowth [32]. In this regard our data seem to recapitulate all these pathogenetic stages, showing deregulation of genes involved in the inflammatory process as well of transcripts that play a role in bone remodeling (i.e., bone growth and bone erosion).…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, it has been recently suggested that Wnt signaling may take part to the process of ankylosis in spondyloarthritis [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Dkk1 heterozygous KO mice showed a high bone mass phenotype [44], and Dkk1 -overexpressing transgenic mice had a low bone mass phenotype [45]. In addition, severe destruction in spine tissues was observed in 3- and 6-month old β-catenin ( ex3 ) Col2CreER mice, including progressive loss of growth plate and endplate cartilage, disorganized annulus fibrosus and nucleus pulposus tissues, and increased osteophyte formation in the disc of the entire spine [34••, 46••]. These studies suggest that the activation of β-catenin signaling may contribute to the development and progression of SpA.…”
Section: Wnt/β-catenin Signaling In Spamentioning
confidence: 99%
“…In addition to its dispensable roles in the development of T cells and the immune system, mounting evidence has recently suggested that it is involved in the pathogenesis of many types of autoimmune diseases, including rheumatoid arthritis (RA), SLE, spondyloarthritis (PsA), and ankylosing spondylitis (AS) [1217]. In SLE patients, aberrant Wnt/ β -catenin signaling was observed in both peripheral B and T cell fractions [18].…”
Section: Introductionmentioning
confidence: 99%